Impact of access to NCI‐ and NCCN‐designated cancer centers on outcomes for multiple myeloma patients: A SEER registry analysis. Issue 4 (13th November 2015) - Ailawadhi, Sikander; Advani, Pooja; Yang, Dongyun; Ghosh, Radhika; Swaika, Abhisek; Roy, Vivek; Foran, James; Colon‐Otero, Gerardo; Chanan‐Khan, Asher
Abstract : BACKGROUND: National Cancer Institute (NCI)/National Comprehensive Cancer Network (NCCN)–designated cancer centers (CCs) offer patients state‐of‐the‐art treatment, but their impact on multiple myeloma (MM) patient outcomes has not been evaluated. METHODS: Adult MM patients diagnosed between 1973 and 2011 were identified from the Surveillance, Epidemiology, and End Results database and were stratified by the county of residence at the time of diagnosis and the year of CC designation. The influence of NCI/NCCN CC access, race, and the year of diagnosis on overall survival (OS) was evaluated with a Cox regression model. RESULTS: A statistically significant OS improvement was noted in patients diagnosed after 1995 with access to 2 or more NCI CCs overall ( P  = .002 for 1996‐2002; P  < .001 for 2003‐2011) and by race for whites (hazard ratio [HR] for 1996‐2002, 0.85; 95% confidence interval [CI], 0.78‐0.91; HR for 2003‐2011, 0.85; 95% CI, 0.79‐0.91) but not for nonwhites. For NCCN access, improvement was seen in 1996‐2002 ( P  = .003), in 2003‐2011 ( P  < .001), and by race for whites (HR, 0.917; 95% CI, 0.88‐0.95) and nonwhites (0.94; 95% CI, 0.89‐0.99), but within nonwhites, this was true only for African Americans (AAs; HR, 0.88; 95% CI, 0.81‐0.97) and not for Asians, Hispanics, or Native Americans. CONCLUSIONS: Improvement in OS was seen in MM patients diagnosed after 1995 with access to 1 NCCN CC or 2 or more NCI CCs. NCI access benefited only whites, whereas NCCN access benefited only white and AA patients. No OS benefit was seen for any subgroup with access to only 1 NCI center. Eliminating racial disparities in health care access and utilization is needed to improve outcomes. Cancer 2016;122:618–625. © 2015 American Cancer Society . Abstract : The influence of National Cancer Institute/National Comprehensive Cancer Network cancer center access, race, and the year of diagnosis on overall survival is evaluated in multiple myeloma patients. Improvements in overall survival are seen in patients diagnosed after 1995 with access to 1 National Comprehensive Cancer Network center or 2 or more National Cancer Institute centers. National Cancer Institute access benefits only whites, whereas National Comprehensive Cancer Network access benefits only whites and African Americans.